Compatibility and effect of capacity ratios between Na3V2(PO4)3 and hard carbon in highly concentrated sodium bis (fluorosulfonyl) imide electrolyte - Quy Phuong Chau; Thanh Liem Pham; Dinh Quan Nguyen; My Loan Phung Le; Van Man Tran; Thien Trung Nguyen (CTU Journal of Innovation and Sustainable Development)
From the standpoint of preserving the Earth's resources and ensuring the long-term viability of humanity, it is imperative to transition away from lithium-ion batteries. High-performance and safe sodium-ion batteries have recently emerged as promising advanced batteries for application in stationary energy storage, attributed to their low cost and abundance of sodium ion. We demonstrate the compatibility and effect of the negative-positive capacity ratio in full-cell Na3V2(PO4)3 and hard carbon in high-concentration electrolytes. Thanks to the excellent oxidation stability of the electrolyte, during 100 cycles, the full cell with a negative-positive capacity ratio of 1.1 demonstrated a consistent capacity of around 100 mAh g-1 with a capacity retention of 90.7%, whereas the full cell with a ratio of 1.0 showed a steady discharge capacity of roughly 90 mAh g-1 with a capacity retention of approaching 100% at a current density of C/5.